Theoretical Investigation of the Photoexcited NO2+H2O reaction at the Air–Water Interface and Its Atmospheric Implications. Issue 61 (24th September 2019) - Martins‐Costa, Marilia T. C.; Anglada, Josep M.; Francisco, Joseph S.; Ruiz‐López, Manuel F.
Abstract: The atmospheric role of photochemical processes involving NO2 beyond its dissociation limit (398 nm) is controversial. Recent experiments have confirmed that excited NO2 * beyond 420 nm reacts with water according to NO2 * +H2 O→HONO+OH. However, the estimated kinetic constant for this process in the gas phase is quite small ( k ≈10 −15 –3.4×10 −14  cm 3  molecule −1  s −1 ) suggesting minor atmospheric implications of the formed radicals. In this work, ab initio molecular dynamics simulations of NO2 adsorbed at the air–water interface reveal that the OH production rate increases by about 2 orders of magnitude with respect to gas phase, attaining ozone reference values for NO2 concentrations corresponding to slightly polluted rural areas. This finding substantiates the argument that chemistry on clouds can be an additional source of OH radicals in the troposphere and suggests directions for future laboratory experimental studies. Abstract : Simulations reveal that the photochemistry of NO2 beyond its dissociation limit might be an additional yet unknown source of OH radicals in the troposphere when it is adsorbed at the air–water interface of cloud droplets.